Incidental De Novo Cerebral Microhemorrhages are Predictive of Future Symptomatic Macrohemorrhages After Surgical Revascularization in Moyamoya Disease. Issue 1 (27th July 2020) - Li, Yiping; Esene, Ignatius; Mandel, Mauricio; Bigder, Mark; Steinberg, Gary K
Abstract: BACKGROUND: Patients with moyamoya disease who develop incidental cerebral microhemorrhages (CMHs) on magnetic resonance imaging (MRI) have higher risk of developing subsequent symptomatic repeat macro hemorrhages. OBJECTIVE: To evaluate the effect of surgical revascularization on development of de novo CMHs and assess its correlation with repeat hemorrhage rates and functional outcome in hemorrhagic onset moyamoya disease (HOMMD). METHODS: We retrospectively reviewed a prospectively managed departmental database of all patients presenting with HOMMD treated between 1987 and 2019. The search yielded 121 patients with adequate MRI follow-up for inclusion into the study. RESULTS: In total, 42 preoperative CMHs were identified in 18 patients (15%). Patients presenting with preoperative CMH were more likely to develop de novo CMH after surgical revascularization. 7 de novo CHMs were identified in 6 patients (5%) on routine postoperative MRI at distinct locations from previous sites of hemorrhage or CMH. Symptomatic repeat macro hemorrhage was confirmed radiographically in 15 patients (12%). A total 5 (83%) of 6 patients with de novo CMHs later suffered symptomatic repeat macro hemorrhage with 4 of 5 (80%) hemorrhages occurring at sites of previous CMH. On univariate and multivariate analysis, de novo CMHs was the only significant variable predictive for developing repeat symptomatic hemorrhage. Development of delayed repeat symptomatic hemorrhage was prognostic for higher modified Rankin Score and therefore poorer functional status, whereas preoperative functional status was predictive of final outcome. CONCLUSION: De novo CMHs after surgical revascularization might serve as a radiographic biomarker for refractory disease and suggest patients are at risk for future symptomatic macro hemorrhage.